Internal and External Barriers to Arabic Reading Mastery: An Empirical Study in an Indonesian Islamic Junior High School - Tri Lasti Br Karo,; Zulfahmi Lubis, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to describe the types of difficulties students face in Arabic reading (qirÄÊ¾ah) skills and to identify the internal and external factors influencing these challenges, including the strategies employed by teachers to address them. Employing a qualitative descriptive approach, data were collected through classroom observation, interviews, and documentation. The research subjects were seventh-grade students at MTs Sirajul Huda Tigabinanga Karo. The findings reveal that students struggle with basic literacy skills such as hijaiyah letter recognition, low motivation, and negative perceptions of Arabic. External factors such as limited teacher availability, inadequate learning support, and scarce instructional materials further exacerbate these difficulties. Nevertheless, teachers have adopted contextual strategies such as daily vocabulary routines and the integration of Islamic values to enhance studentsâ€™ qirÄÊ¾ah abilities. This study recommends context-based interventions and institutional support to promote more effective reading instruction in resource-constrained madrasah settings.